Hate Crimes as Discriminatory Violations - Mihajlova Stratilati Elena (LeXonomica, 2017)
Hate crimes are new concept in the academic research. Clearly, they are not a new phenomenon and it is important to bear in mind that what is currently being addressed as "hate crimes" has a long historical line. What is however new in this context is the cultural plurality of societies as a result of increased migration and postmodern awakening of old identities. Not to forget the strong role that globalization has in the facing of cultures to each other. Thus, the hate crimes that are otherwise older are placed in this new context. The first part of the text gives an overview of some of the wider and more elaborated definitions that are central for our conceptual understanding of hate crimes. Following this understanding the second part of the text tries to analyse the unique harm or injury that hate crimes are causing and to illuminate more precisely the discriminatory violence and how it brings further humiliation to the victim.